Indwelling Peritoneal Catheters for Managing Malignancy-Associated Ascites. Issue 4 (December 2015) - Wong, Benson Chun To; Cake, Lorraine; Kachuik, Lynn; Amjadi, Kayvan
We investigated use of the tunnelled catheter in a large palliative population with malignancy-associated ascites employing retrospective analysis of a prospectively maintained patient database of tunnelled peritoneal catheter insertions for refractory malignancy-associated ascites or new rapidly accumulating ascites. We found that a 100 percent procedural success rate was achieved with 395 tunnelled catheters inserted in 386 patients. Catheters remained In situ for 66 days, on average. In a total of 22 cases (5.57 percent), complications developed. Nonfatal Infections occurred most commonly — in 15 cases (3.80 percent). Ascites stopped reaccumulating in 16 cases (4.05 percent), leading to catheter removal. The mean Baseline Dyspnea Index was 3.79 (95 percent confidence interval [CI], 3.64-3.94); the mean Transitional Dyspnea Index postinsertion was 5.14 (95 percent CI, 4.94–5.34). In all, 13 patients completed serial European Organisation for Research and Treatment of Cancer Quality of Life Questionnaires. Postinsertion, overall quality of life improved significantly (p<0.05), as did all functional domains and fatigue, pain, dyspnea, and appetite symptoms. The tunnelled peritoneal catheter is feasible and safe and causes minimal complications. Its use results in significant improvement in dyspnea and improvement in overall quality of life for a small number of patients.